Exergy analysis of a plate heat exchanger with a new geometric design - Shamsdanesh, R.; Jafarmadar, S.; Javani, N. (SPRINGER, 2021)
In the current study, a plate heat exchanger with a novel geometry is investigated in which the cross section is not uniform as in conventional ones. New configurations of plate heat exchangers and obtained the best model by considering entropy generation, heat transfer improvement number and effectiveness. Different non-uniform cross-sectional configurations have been investigated with different flow directions and various arrangements such as cold and hot flow rates from the inlet side to the outlet side or vice versa. Three-dimensional models of the plate heat exchanger are investigated numerically for nine different configurations to investigate the effect of the geometry, thermodynamic and hydraulic characteristics on the plate heat exchanger effectiveness. The entropy generation, the heat transfer effectiveness, NTU as the number of transfer units and heat exchanger reversibility norm are among the main considered parameters in these schemes. The results show a 46% enhancement in the heat transfer rate, 10% increment in heat transfer improvement number and 57% increment in the effectiveness of the new heat exchanger compared to the conventional heat exchangers.
Keywords: Entropy generation; Exergy destruction; Effectiveness; Plate heat exchanger; Thermal performance; MANY-OBJECTIVE OPTIMIZATION; PERFORMANCE; ENHANCEMENT; ALGORITHM; SYSTEM; ENERGY; PIPE; Thermodynamics; Chemistry